Effects of concurrent visual tasks on cortico-muscular synchronization in humans - Mat Safri, Norlaili; Murayama, Nobuki; Hayashida, Yuki; Igasaki, Tomohiko (Elsevier B.V., 2007)
To study the effects of external visual stimulation on motor cortex-muscle synchronization, coherence between electroencephalography (EEG) and electromyography (EMG) was measured in normal subjects under Before, Task (visual task: Ignore or Count, or arithmetic task) and After conditions. The control (Before and After) conditions required the subject to maintain first dorsal interosseous muscle contraction without visual stimulation. In the visual task, a random series of visual stimuli were displayed on a screen while the subjects maintained the muscle contraction. The subjects were asked to ignore the stimuli in the Ignore condition and to count certain stimuli in the Count condition. Also, in the arithmetic task, the subjects were asked to perform a simple subtraction. The EEG“EMG coherence found at C3 site at 13“30 Hz (beta) was increased and sustained in magnitude during the Ignore and Count conditions, respectively. To examine the cause of the change of coherence, changes of EEG and EMG spectral power were computed for each frequency band. There was little change in the EMG spectral power in any frequency bands. While the spectral power of EEG unchanged in the beta band, it significantly increased and decreased in the range of 8â€“12 Hz and of 31â€“50 Hz, respectively, for both Ignore and Count conditions, not only at the C3 site but at various sites as well. These results were in contrast to those obtained for the arithmetic task: the beta band EEG“EMG coherence was attenuated and the EEG spectral power at 4“7 Hz and at 31“50 Hz were significantly increased and decreased, respectively. As a conclusion, the present results are consistent with the idea that the enhanced 8“12 Hz/decreased 31“50 Hz oscillations affect strength of the beta band cortico-muscular synchronization by suppressing the visual processing.